MV-Flow imaging for evaluating the placental function of gestational diabetes mellitus - Song, Jiahao; Li, Xiaobin; Zhu, Chen; Sun, Hongshuang; Ren, Yunyun (Frontiers in Endocrinology, 2025)
BackgroundGestational diabetes mellitus (GDM) is characterized by vascular dysfunction and is associated with adverse perinatal outcomes for both the mother and fetus. Microvascular index (MVI) is a non-invasive marker of microvascular function assessed by microvascular flow imaging (MV-Flow). This study aimed to evaluate the performance of conventional Doppler ultrasound and MV-Flow in delineating the placental microvessels and to explore the feasibility and potential clinical value of using MV-Flow for placental function in GDM women.MethodsThis study included women with singleton pregnancies at 28–36 weeks of gestation and was conducted between November 2023 and January 2025. All women underwent routine prenatal ultrasound and MV-Flow. GDM women were stratified into two subgroups by glycated hemoglobin A1c (HbA1c) value: GDM1 (HbA1c ≤ 5.5%) and GDM2 (HbA1c > 5.5%). Comparisons of data were made using parametric and non-parametric tests between the non-GDM group and the GDM group. Correlation between MVImean and neonate birthweight was assessed using Pearson’s correlation coefficient. Multivariate analysis was performed using general linear regression models of factors associated with GDM. Receiver operating characteristic curve analysis was conducted to determine the optimal MVI threshold for distinguishing between participants with GDM and those without.ResultsThe study population included 92 controls and 88 women with GDM. In the GDM group, compared to the control, there was significantly higher MVImean of placenta (P = 0.031). There was no significant difference between the GDM2 group and the control group in terms of MVImean. There was a moderate correlation of placental MVImean with neonate birthweight (r = 0.539; P < 0.001). Based on the Youden index, the placental MVImean threshold that best discriminated between participants with GDM and those without was 38.95%, with a maximum achievable sensitivity of 62.9% and a specificity of 69.6%.ConclusionsPlacental microvascular blood flow can be visualized and quantified in women with GDM using MV-Flow.